Upconversion Properties of NaGd(WO4)2:Ho3+/Yb3+ Yellow Phosphors Synthesized by Cyclic Microwave-Modified Sol-Gel Method - Sung Lim, Chang (Asian Journal of Chemistry, 2015)
Upconversion properties of the NaGd1-x(WO4)2:Ho3+/Yb3+ yellow phosphors with doping concentrations of Ho3+ and Yb3+ (x = Ho3+ + Yb3+, Ho3+ = 0.05, 0.1, 0.2 and Yb3+ = 0.2, 0.45) were investigated. The synthesized particles were successfully synthesized by the micro-wave-modified sol-gel method. Well-crystallized particles showed a fine and homogeneous morphology with particle sizes of 2-5 μm. Under excitation at 980 nm, the upconversion intensity of NaGd0.5(MoO4)4:Ho0.05Yb0.45 phosphors exhibited yellow emissions based on a strong 550 nm emission band in the green region and a very strong 655 nm emission band in the red region. The Raman spectra of the particles indicated the presence of strong peaks at higher frequencies.